Identification and characterization of atypical enteropathogenic and Shiga toxin-producing Escherichia coli isolated from ground beef and poultry breast purchased in Botucatu, Brazil - Tanabe, Rodrigo H. S. [UNESP]; Vieira, Melissa A. [UNESP]; Mariano, Noelle A. B. [UNESP]; Dias, Regiane C. B. [UNESP]; da Silva, Rafael Ventin; Castro, Caroline M. [UNESP]; dos Santos, Luis F.; Camargo, Carlos H.; Yamatogi, Ricardo S. [UNESP]; Rall, Vera L. M. [UNESP]; Hernandes, Rodrigo T. [UNESP] (Springer Nature, 2019)
Atypical enteropathogenic (serotypes O4:H16, O8:H25, O68:H2, O105:H7, and OR:H25) and Shigatoxigenic (ONT:H46) Escherichia coli were isolated from samples of ground beef and poultry breast purchased in Botucatu, Brazil. Phenotypic and molecular characterization indicated the potential of these isolates to adhere to host epithelial cells and cause damage.
Keywords: EPEC; Genotyping; Ground beef; Pathogenesis; Poultry breast and diarrhea; STEC